(p, q)-th order oriented growth of composite entire and meromorphic functions on the basis of their integer translation. Issue 2 (17th February 2019) - Biswas, Ritam
Abstract: The principal objective of this paper is to investigate some results related to the growth rates of the composition of integer translated entire and meromorphic functions depending upon the discussion about the growth properties of their ( p, q )-th order for any two positive integers p and q .